Resource-use optimization across the age gap: Older adults less effectively modulate their mind-wandering than young - Dr Paul Seli, Ph.D.; Kevin O'Neill (Open Science Framework, 2022)
Preregistration, data, and materials used in Seli et al.'s paper entitled: " Resource-use optimization across the age gap: Older adults less effectively modulate their mind-wandering than young"